Pre-lithiated silicon monoxide composite material and cycle performance evaluation method
By coating and prelithiating silicon oxide, preliminarily lithium silicon oxide composite material with core-shell structure was prepared, and by comprehensively considering the evaluation method of multiple core parameters, the silicon-based negative electrode material in lithium-ion batteries was solved. The problem of reduced circulation performance caused by the medium volume effect has achieved improvement in battery circulation performance and stability.
Patent Information
- Application Number
- CN202310979991.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-04
- Publication Date
- 2025-02-14
AI Technical Summary
The existing silicon-based negative electrode active materials have serious volume effects in lithium-ion batteries, resulting in the pulverization of the electrode material and the separation of the electrode material from the current collector, reducing the cycling performance of the battery.
By coating and prelithiating silicon oxide, a prelithium silicon oxide composite material with a core-shell structure was prepared, and a cyclic performance evaluation method was proposed. By comprehensively considering particle size, silicon grain size, and coating The four core parameters of layer quality and integrity are calculated to obtain the cyclic performance index Y to ensure that Y is greater than or equal to 0.1 to achieve good cyclic performance.
The circulation performance of prelithium silicon oxide composite materials has been improved, extending the cycle cycle of the battery, and improving the energy density and stability of the battery.
Smart Images

Figure CN119447209A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a pre-lithiation silicon oxide composite material and a method for evaluating cycle performance. Background Art
[0002] At present, the negative electrode active material of commercial lithium-ion batteries is mainly graphite, but due to its low theoretical capacity (about 372mAh / g), it limits the further improvement of the energy density of lithium-ion batteries. Since the theoretical capacity of silicon-based negative electrode active materials is about 10 times that of current commercial graphite negative electrode active materials, it has broad application prospects, so silicon-based negative electrode active materials are gradually moving from laboratory research and development to commercial application.
[0003] As the negative electrode active material, elemental silicon has a serious volume effect during the lithium insertion and extraction process, with a volume change rate of about 300%. It will cause the electrode material to pulverize and the electrode material to separate from the current collector, thereby continuously consuming the electrolyte and reducing the cycle performance of the electrode material.
[0004] In order to solve this problem, the researchers coated and pre-lithiated silicon oxide, and used a variety of processes to modify silicon oxide together to obtain a pre-lithiated silicon oxide composite material with a core-shell structure. The pre-lithiated silicon oxide composite material is a high-initial-efficiency silicon-based negative electrode material obtained by reacting lithium metal and silicon oxide. It has obvious advantages in expansion rate and cycle stability, and is easier to realize industrial application than elemental silicon.
[0005] The pre-lithium silicon oxide composite material is a granular powder material, each particle of which is composed of a core and a coating layer. The core includes lithium silicate and nano silicon grains, and the coating layer can be a carbon coating layer, a metal oxide coating layer or an organic coating layer. The particle size, coating quality and integrity, and silicon grain size of the pre-lithium silicon oxide composite material are the core indicators of the pre-lithium silicon oxide composite material, but the various indicators of the pre-lithium silicon oxide composite material are interrelated and restrained. Existing pre-lithium silicon oxide composite material products have problems such as the coating layer is processed completely, but the silicon grains are too large, resulting in cycle degradation, or the silicon grains are suitable but the coating quality is poor. These three indicators are interrelated and restricted during the processing of the pre-lithium silicon oxide composite material. In order to achieve good cycle performance of the pre-lithium silicon oxide composite material, a balanced design is required among these three indicators to obtain a pre-lithium silicon oxide composite material with good cycle performance. Summary of the invention
[0006] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the embodiments of the present invention provide a pre-lithiation silicon oxide composite material and a method for evaluating cycle performance. The composite material reasonably matches the particle size of the composite material, the quality and integrity of the coating layer, the size of the silicon grains and other indicators, so that the composite material has good cycle performance.
[0007] The pre-lithiation silicon oxide composite material of the embodiment of the present invention comprises a core and a coating layer coated on the surface of the core, wherein the core comprises pre-lithiation silicon oxide, and the cycle performance index of the composite material is marked as Y, where Y=a(-D 50 2 +17D 50 -60)+b×d Si +c(-ω C 2 +7ω C )+dL, where a=0.2, b=-0.1, c=0.15, d=-0.5, D 50 is the particle size of the composite material, in μm, d Si is the particle size of silicon grains in the pre-lithiation silicon oxide, in nm, ω C is the mass fraction of the coating layer in the composite material, in %, L is the gas production of the composite material, in mL / g; Y is greater than or equal to 0.1.
[0008] The advantages and technical effects brought by the pre-lithiation silicon dioxide composite material of the embodiment of the present invention are:
[0009] (1) The composite material of the embodiment of the present invention comprehensively considers the influence of four core parameters, namely, particle size, silicon grain size, coating layer mass fraction and coating layer integrity, on the cycle performance of the composite material, finds the relationship between the four core parameters and the cycle performance of the composite material, and uses the Y value to characterize the quality of the cycle performance of the composite material;
[0010] (2) The composite material of the embodiment of the present invention is designed to match the above four parameters. For example, when the coating layer is completely processed, by limiting Y to be greater than or equal to 0.1, a suitable silicon grain size range can be obtained, which will not make the silicon grain size too large, and thus will not deteriorate the cycle performance of the composite material. Or, when the silicon grain size is appropriate, by limiting Y to be greater than or equal to 0.1, it can be obtained under what conditions the coating layer quality is good, and thus will not deteriorate the cycle performance of the composite material. The matching relationship between other parameters is also achieved in a similar manner.
[0011] (3) The composite material of the embodiment of the present invention has a particle size D of the composite material 50 , the particle size d of silicon grains in pre-lithiation silicon oxide Si, the mass fraction of the coating layer in the composite material ω C The gas production L of the composite material reflecting the integrity of the coating layer is matched and designed so that these four parameters satisfy the above relationship Y and Y is greater than or equal to 0.1, and the obtained composite material has good cycle performance.
[0012] In some embodiments, the cycle performance index Y of the composite material is greater than or equal to 0.4.
[0013] In some embodiments, the cycle performance index Y of the composite material is greater than or equal to 0.7.
[0014] In some embodiments, the particle size D of the composite material 50 7.5-10μm.
[0015] In some embodiments, the particle size d of the silicon grains in the pre-lithiation silicon oxide is Si 1-8nm.
[0016] In some embodiments, the mass fraction of the coating layer in the composite material is C 1-8%.
[0017] In some embodiments, the gas generation amount L of the composite material is less than 0.2 mL / g.
[0018] In some embodiments, the coating layer is a carbon coating layer.
[0019] The embodiment of the present invention also provides a method for evaluating the cycle performance of a pre-lithiation silicon dioxide composite material, wherein the composite material comprises a core and a coating layer coated on the surface of the core, wherein the core comprises pre-lithiation silicon dioxide, and the evaluation method comprises the following steps:
[0020] The cycle performance index of the composite material is set to Y, Y = a(-D 50 2 +17D 50 -60)+b×d Si +c(-ω C 2 +7ω C )+dL, where a=0.2, b=-0.1, c=0.15, d=-0.5, D 50 is the particle size of the composite material, in μm, d Si is the particle size of silicon grains in the pre-lithiation silicon oxide, in nm, ω C is the mass fraction of the coating layer in the composite material, in %, and L is the gas production of the composite material, in mL / g;
[0021] According to the particle size D of the composite material50 , the particle size d of the silicon grains in the pre-lithiation silicon oxide Si , the mass fraction of the coating layer in the composite material ω C The gas production L of the composite material is used to calculate the cycle performance index Y of the composite material. The larger the Y is, the better the cycle performance of the composite material is.
[0022] The advantages and technical effects brought by the evaluation method of the cycle performance of the pre-lithiation silicon dioxide composite material of the embodiment of the present invention are:
[0023] The evaluation method of the embodiment of the present invention comprehensively considers the influence of four core parameters of the composite material, namely, particle size, silicon grain size, coating mass fraction and coating integrity, on the cycle performance of the composite material, finds the relationship between these four core parameters and the cycle performance of the composite material, and uses the Y value to characterize the quality of the cycle performance of the composite material. Therefore, through the evaluation method of the embodiment of the present invention, the quality of the cycle performance of the composite material can be quickly predicted before being assembled into a battery, and the evaluation result has a high accuracy.
[0024] In some embodiments, when Y is greater than or equal to 0.1, the number of cycles at which the capacity of the composite material decays to 80% of the initial capacity is greater than or equal to 400 cycles; when Y is greater than or equal to 0.4, the number of cycles at which the capacity of the composite material decays to 80% of the initial capacity is greater than or equal to 450 cycles; when Y is greater than or equal to 0.7, the number of cycles at which the capacity of the composite material decays to 80% of the initial capacity is greater than or equal to 500 cycles.
[0025] In some embodiments, the method for determining the gas production L of the composite material is as follows: the composite material with a mass of m is mixed with a binder and deionized water to obtain a test slurry and sealed, and the weight of the water displaced is tested by the drainage method to obtain the weight M1, and then after being placed at room temperature, the weight of the water displaced is tested by the drainage method to obtain the weight M2, L = (M1-M2) / (ρ 水· m). BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 Schematic diagram of the preparation method of the pre-lithiation silicon dioxide composite material according to an embodiment of the present invention; the dark grey part in the left figure is the carbon coating layer. DETAILED DESCRIPTION
[0027] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.
[0028] The embodiment of the present invention provides a pre-lithiation silicon oxide composite material, comprising a core and a coating layer coated on the surface of the core, wherein the core comprises pre-lithiation silicon oxide, and the cycle performance index of the composite material is Y, where Y=a(-D 50 2 +17D 50 -60)+b×d Si +c(-ω C 2 +7ω C )+dL, where a=0.2, b=-0.1, c=0.15, d=-0.5, D 50 is the particle size of the composite material, in μm, d Si is the particle size of silicon grains in the pre-lithiation silicon oxide, in nm, ω C is the mass fraction of the coating layer in the composite material, in %, L is the gas production of the composite material, in mL / g; Y is greater than or equal to 0.1.
[0029] In the composite material of the embodiment of the present invention, the particle size D of the composite material is 50 , the particle size d of silicon grains in pre-lithiation silicon oxide Si , the mass fraction of the coating layer in the composite material ω C The gas production L of the composite material reflecting the integrity of the coating layer is matched and designed so that the four parameters satisfy the above relationship Y and Y is greater than or equal to 0.1, so that the composite material has good cycle performance.
[0030] In some embodiments, the cycle performance index Y of the composite material is greater than or equal to 0.4. When Y is too small, battery capacity decay is likely to occur, which is not conducive to improving the cycle performance of the negative electrode material. In order to make the composite material have excellent cycle performance, preferably, in some embodiments, the cycle performance index Y of the composite material is greater than or equal to 0.7.
[0031] In some embodiments, the particle size D of the composite material 50 is 7.5-10 μm, for example, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm, etc. 50 If D is too small, Y is also too small, which will have an adverse effect on the cycle performance. 50 When it is too large, Y is also too small, which will have an adverse effect on the cycle performance.
[0032] In some embodiments, the particle size d of the silicon grains in the pre-lithiation silicon oxide is Si is 1-8nm, for example, 1nm, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, etc. When d SiIf d is too small, Y is also too small, which will have an adverse effect on the cycle performance. Si When it is too large, Y will also be smaller, which will have an adverse effect on the cycle performance.
[0033] In some embodiments, the mass fraction of the coating layer in the composite material is C is 1-8%, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, etc. C If it is too small, Y is also too small, which will have an adverse effect on the cycle. C When it is too large, Y is also too large, which will have an adverse effect on the cycle.
[0034] In some embodiments, the gas production L of the composite material is less than 0.2 mL / g, for example, 0.01 mL / g, 0.05 mL / g, 0.08 mL / g, 0.1 mL / g, 0.12 mL / g, 0.15 mL / g, 0.8 mL / g, 0.2 mL / g, etc. When L is too large, Y is also too large, which will have an adverse effect on the cycle.
[0035] The composite material of the embodiment of the present invention has no particular limitation on the type of material of the coating layer, and may be, for example, a carbon coating layer, a metal oxide coating layer, or an organic coating layer, etc. In order to better reduce the volume expansion and contraction of the silicon oxide material in subsequent charge and discharge cycles, thereby improving the cycle performance of the negative electrode material, preferably, in some embodiments, the coating layer is a carbon coating layer.
[0036] The embodiment of the present invention also provides a method for evaluating the cycle performance of a pre-lithiation silicon dioxide composite material, wherein the composite material comprises a core and a coating layer coated on the surface of the core, wherein the core comprises pre-lithiation silicon dioxide, and the evaluation method comprises the following steps:
[0037] The cycle performance index of the composite material is set to Y, Y = a(-D 50 2 +17D 50 -60)+b×d Si +c(-ω C 2 +7ω C )+dL, where a=0.2, b=-0.1, c=0.15, d=-0.5, D 50 is the particle size of the composite material, in μm, d Si is the particle size of silicon grains in the pre-lithiation silicon oxide, in nm, ω C is the mass fraction of the coating layer in the composite material, in %, and L is the gas production of the composite material, in mL / g;
[0038] According to the particle size D of the composite material 50 , the particle size d of the silicon grains in the pre-lithiation silicon oxide Si , the mass fraction of the coating layer in the composite material ω C The gas production L of the composite material is used to calculate the cycle performance index Y of the composite material. The larger the Y is, the better the cycle performance of the composite material is.
[0039] In industrial production, it is often necessary to test or estimate the cycle performance of the produced pre-lithium silicon oxide composite materials. The usual testing method is to assemble the composite material into a test battery to test its cycle performance, so as to determine whether the composite material is qualified. However, this testing method is time-consuming and labor-intensive, and has low efficiency. The estimation method is to qualitatively judge the quality of the composite material's cycle performance by comprehensively considering the core parameters such as the particle size of the composite material, the quality and integrity of the coating layer, and / or the size of the silicon grains. For example, when the coating layer is processed completely but the silicon grains are too large, it is easy to cause cycle degradation, or when the silicon grain size is appropriate but the coating layer quality is poor, it will also cause cycle degradation problems. However, since the quality of the cycle performance of the pre-lithium silicon oxide composite material is determined by these key indicators, and these indicators are interrelated and constrained, this estimation method is difficult to accurately compare the cycle performance of various pre-lithium silicon oxide composite materials.
[0040] The evaluation method of the embodiment of the present invention comprehensively considers the influence of four core parameters of the composite material, namely, particle size, silicon grain size, coating mass fraction and coating integrity on the cycle performance of the composite material, finds the relationship between these four core parameters and the cycle performance of the composite material, and uses the Y value to characterize the quality of the cycle performance of the composite material. Therefore, through the evaluation method of the embodiment of the present invention, the quality of the cycle performance of the composite material can be quickly predicted before being assembled into a battery, and the judgment result is accurate. There is no need to assemble a test battery to test its cycle performance, which is conducive to saving time and improving efficiency.
[0041] In some embodiments, when Y is greater than or equal to 0.1, the number of cycles when the capacity of the composite material decays to 80% of the initial capacity is greater than or equal to 400 cycles, indicating good cycle performance; when Y is greater than or equal to 0.4, the number of cycles when the capacity of the composite material decays to 80% of the initial capacity is greater than or equal to 450 cycles, indicating excellent cycle performance; when Y is greater than or equal to 0.7, the number of cycles when the capacity of the composite material decays to 80% of the initial capacity is greater than or equal to 500 cycles, indicating excellent cycle performance. According to the above judgment criteria, the number of cycles of the composite material can be easily estimated.
[0042] In some embodiments, the method for determining the gas production L of the composite material is as follows: the composite material with a mass of m is mixed with a binder and deionized water to obtain a test slurry and sealed, and the weight of the water displaced is tested by the drainage method to obtain the weight M1, and then after being placed at room temperature, the weight of the water displaced is tested by the drainage method to obtain the weight M2, L = (M1-M2) / (ρ 水· m).
[0043] The present invention is described in detail below with reference to the embodiments and the accompanying drawings.
[0044] Example 1
[0045] A pre-lithiation silicon oxide composite material, comprising a core and a coating layer coated on the surface of the core, wherein the core comprises pre-lithiation silicon oxide, and the cycle performance index of the composite material is Y, where Y=a(-D 50 2 +17D 50 -60)+b×d Si +c(-ω C 2 +7ω C )+dL, where a=0.2, b=-0.1, c=0.15, d=-0.5, D 50 is the particle size of the composite material, in μm, d Si is the particle size of silicon grains in the pre-lithiation silicon oxide, in nm, ω C is the mass fraction of the coating layer in the composite material, in %, L is the gas production of the composite material, in mL / g; Y is greater than or equal to 0.1. 50 7.5 μm, d Si is 2nm, ω C is 2%, L is 0.15 mL / g, and Y is calculated to be 0.48.
[0046] Example 2
[0047] The pre-lithiation silicon dioxide composite material with a core-shell structure in this embodiment is the same as that in embodiment 1, except that: 50 8.5 μm, d Si is 2nm, ω C is 2%, L is 0.1 mL / g, and Y is calculated to be 0.7.
[0048] Example 3
[0049] The pre-lithiation silicon dioxide composite material with a core-shell structure in this embodiment is the same as that in embodiment 1, except that: 50 9.5 μm, d Si is 2nm, ω Cis 2%, L is 0.1 mL / g, and Y is calculated to be 0.5.
[0050] Example 4
[0051] The pre-lithiation silicon dioxide composite material with a core-shell structure in this embodiment is the same as that in embodiment 1, except that: 50 8.5 μm, d Si 5nm,ω C is 2%, L is 0.1 mL / g, and Y is calculated to be 0.4.
[0052] Example 5
[0053] The pre-lithiation silicon dioxide composite material with a core-shell structure in this embodiment is the same as that in embodiment 1, except that: 50 8.5 μm, d Si 8nm,ω C is 2%, L is 0.1 mL / g, and Y is calculated to be 0.1.
[0054] Example 6
[0055] The pre-lithiation silicon dioxide composite material with a core-shell structure in this embodiment is the same as that in embodiment 1, except that: 50 8.5 μm, d Si 5nm,ω C is 3.5%, L is 0.05 mL / g, and Y is calculated to be 0.76.
[0056] Example 7
[0057] The pre-lithiation silicon dioxide composite material with a core-shell structure in this embodiment is the same as that in embodiment 1, except that: 50 8.5 μm, d Si 5nm,ω C is 5%, L is 0.05 mL / g, and Y is calculated to be 0.43.
[0058] Example 8
[0059] A method for evaluating the cycle performance of a pre-lithiation silicon dioxide composite material having a core-shell structure, the composite material comprising a core and a coating layer coated on the surface of the core, the core comprising pre-lithiation silicon dioxide, the evaluation method comprising the following steps:
[0060] The cycle performance index of the composite material is set to Y, Y = a(-D 50 2 +17D 50 -60)+b×d Si +c(-ω C 2 +7ωC )+dL, where a=0.2, b=-0.1, c=0.15, d=-0.5, D 50 is the particle size of the composite material, in μm, d Si is the particle size of silicon grains in the pre-lithiation silicon oxide, in nm, ω C is the mass fraction of the coating layer in the composite material, in %, and L is the gas production of the composite material, in mL / g;
[0061] Determine the particle size D of the composite material 50 , the particle size d of the silicon grains in the pre-lithiation silicon oxide Si , the mass fraction of the coating layer in the composite material ω C The gas production L of the composite material is used to calculate the cycle performance index Y of the composite material. The larger the Y is, the better the cycle performance of the composite material is.
[0062] It should be noted that the particle size d of the silicon grains in the pre-lithiation silicon oxide is Si The results were obtained by the following test methods: (1) 1 g of pre-lithiated silicon dioxide powder was placed in an XRD sample trough to prepare three parallel samples; (2) the sample was scanned at a scanning speed of 2° / min with an angle range of 5°-60°; (3) the Scherrer formula was used to calculate the half-peak width of 27°, d Si =Kλ / (βcosθ), K is a constant, λ is the wavelength of X-rays, β is the half-width of the diffraction peak, and θ is the diffraction angle, and the silicon grain size can be obtained.
[0063] Evaluation results: Comparing the calculation results of the Y values of Examples 1-7, the Y values are ranked from large to small as Example 6> Example 2> Example 3> Example 1> Example 7> Example 4> Example 5. According to the principle that the larger the Y, the better the cycle performance of the composite material, it is judged that the ranking of the cycle performance from high to low should be Example 6> Example 2> Example 3> Example 1> Example 7> Example 4> Example 5.
[0064] Verification of the accuracy of the evaluation results: The pre-lithiation silicon dioxide composite materials of Examples 1-7 were prepared, and then assembled into test batteries and their cycle performance was tested. The actual cycle performance test results were compared with the estimated results of the evaluation method of this embodiment to verify the accuracy of the evaluation method of this embodiment. The specific steps are as follows.
[0065] S1, such as Figure 1 As shown, the pre-lithiation silicon oxide composite materials of Examples 1-7 were prepared
[0066] Take 20kg of carbon-coated pre-lithium silicon oxide composite material (d Si =2nm,ωC =2%), the carbon-coated pre-lithium silicon oxide composite material is classified into particles of D 50 There are three groups of samples with diameters of 7.5 μm (Example 1), 8.5 μm (Example 2) and 9.5 μm (Example 3).
[0067] Take 10kg of carbon-coated pre-lithium silicon oxide composite material (D 50 =8.5μm,ω C =2%, d Si =2nm), and heat-treated at 800°C for 10h in a nitrogen atmosphere to obtain a carbon-coated pre-lithiation silicon dioxide composite material with a silicon grain size of 5nm, which is the sample of Example 4.
[0068] Take 10kg of carbon-coated pre-lithium silicon oxide composite material (D 50 =8.5μm,ω C =2%, d Si =2nm), and heat-treated at 900°C for 10h in a nitrogen atmosphere to obtain a carbon-coated pre-lithiation silicon dioxide composite material with a silicon grain size of 8nm, which is the sample of Example 5.
[0069] Take 10kg of carbon-coated pre-lithium silicon oxide composite material (D 50 =8.5μm,ω C =2%, d Si =3nm), treated at 800°C for 5h in a mixed atmosphere of nitrogen and acetylene in a tube furnace to obtain a carbon-coated pre-lithium silicon oxide composite material, which is the sample of Example 6;
[0070] Take 10kg of carbon-coated pre-lithium silicon oxide composite material (D 50 =8.5μm,ω C =2%, d Si =3nm), treated in a mixed atmosphere of nitrogen and acetylene in a tube furnace at 800°C for 10h to obtain a carbon-coated pre-lithium silicon oxide composite material, which is the sample of Example 7;
[0071] It should be noted that the above-mentioned slurrying method was used to test the compatibility of the carbon-coated pre-lithiation silicon oxide composite material samples (as negative electrode active materials) and the binder (amino or cyanide monomer content greater than 50wt%, solid content of 10wt%) of Examples 1-7, and the gas production L of each carbon-coated pre-lithiation silicon oxide composite material sample was obtained, which was used to evaluate the coating integrity of the carbon coating layer.
[0072] Specifically, m=10 g of the carbon-coated pre-lithium silicon oxide composite material sample prepared in the above Examples 1-7 was weighed, mixed with 3 g of binder polyacrylate (PAA) and 3 g of deionized water, stirred with an overhead stirrer for 24 h, all the slurry was taken out, and sealed with an aluminum-plastic film, and the weight of the water displaced was tested by the drainage method M1, and then placed at room temperature for 48 h, and then the weight of the water displaced was tested by the drainage method M2, L=(M1-M2) / (ρ 水· m).
[0073] S2. Full battery electrochemical performance test
[0074] ① Preparation of a full battery: The full battery includes a positive electrode sheet and a negative electrode sheet, and an electrolyte system (according to the mass ratio of ethylene carbonate (EC): dimethyl carbonate (DMC): diethyl carbonate (DEC): fluoroethylene carbonate (FEC): vinylene carbonate (VC) = 0.3:0.3:0.3:0.07:0.03), and the negative electrode active material prepared in Example 1-3 is stirred at a speed of 1200 rpm for 2 h according to the mass ratio of conductive carbon black (SP): polyacrylate (PAA): water: single-walled carbon nanotube (SWCNT) = 2.8:46.67:100:20, and then switched to 500 rpm for stirring for standby use. 1 kg of carbon-coated pre-lithium silicon oxide composite material samples (as negative electrode active materials) of each group in Examples 1-3 were added separately and dispersed at a speed of 2500 rpm for 90 s. The slurry was placed for 2 h after slurrying. If the placement time exceeded 30 min, it was dispersed again at a speed of 2500 rpm before coating to control the surface density to 2.0 g / m 2 , control the compaction density to 1.25g / m 3 , and the negative electrode is obtained. The positive electrode is made of NCM ternary material. Assemble the soft pack battery, and let it stand for 12 hours after the battery is assembled;
[0075] ②Test working steps: Formation step: 0.05C charge to 3.5V, 0.1C charge to 3.85V; Constant capacity step: 0.33C charge to 4.3V, discharge to 2.5V, 0.33C charge to 3.85V; Cycle step: cycle temperature is 45℃, charge and discharge 1C / 1C, the number of cycles for the capacity to decay to 80% of the initial capacity is shown in Table 1.
[0076] Table 1. Test results of the physical and chemical properties and cycle performance of the carbon-coated pre-lithiation silicon oxide composite materials of Examples 1-7
[0077]
[0078] It should be noted that the d set in Examples 4, 6, and 7 SiThe reason why the silicon grain size is 5nm instead of 2nm is that: the silicon grain size is closely related to the carbon content. The carbon coating process will lead to the growth of the silicon grains. In the case of 2nm silicon grains, only 2% carbon can be coated. Coating 3.5% and 5% carbon makes it difficult to ensure that the silicon grains are still 2nm. In the case of 5nm silicon grains, 2%, 3.5%, and 5% carbon can be coated. Therefore, the d set in Examples 4, 6, and 7 is Si It is 5nm.
[0079] S3. Verify the accuracy of evaluation results
[0080] As shown in Table 1, the number of cycles for the capacity to decay to 80% of the initial capacity is ranked from most to least as Example 6>Example 2>Example 3=Example 4>Example 1>Example 7>Example 5, which is mostly consistent with the estimated results of Example 8, with only a slight difference in the ranking between Example 1, Example 4 and Example 7. 50 The impact of Si The impact and C From the perspective of their respective influences, the ranking of the measured values of the number of cycles is consistent with the ranking of the Y values, which is consistent with the understanding of the influence rules of the core indicators of the pre-lithiation silicon oxide composite material with a core-shell structure in this field. In summary, the evaluation method of Example 8 has a high accuracy and can be used to predict the cycle performance of the pre-lithiation silicon oxide composite material with a core-shell structure.
[0081] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0082] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A pre-lithiation silicon dioxide composite material, characterized in that: The composite material comprises a core and a coating layer coated on the surface of the core, wherein the core comprises pre-lithium silicon oxide, and the cycle performance index of the composite material is Y, where Y=a(-D 50 2 +17D 50 -60)+b×d Si +c(-ω C 2 +7ω C )+dL, where a=0.2, b=-0.1, c=0.15, d=-0.5, D 50 is the particle size of the composite material, in μm, d Si is the particle size of silicon grains in the pre-lithiation silicon oxide, in nm, ω C is the mass fraction of the coating layer in the composite material, in %, L is the gas production of the composite material, in mL / g; Y is greater than or equal to 0.
1.
2. The pre-lithiation silicon dioxide composite material according to claim 1, characterized in that: The cycle performance index Y of the composite material is greater than or equal to 0.
4.
3. The pre-lithiation silicon dioxide composite material according to claim 2, characterized in that: The cycle performance index Y of the composite material is greater than or equal to 0.
7.
4. The pre-lithiation silicon dioxide composite material according to claim 1, characterized in that: The particle size D of the composite material 50 is 7.5-10 μm; and / or, the particle size d of the silicon grains in the pre-lithiation silicon oxide Si 1-8nm.
5. The pre-lithiation silicon dioxide composite material according to claim 1, characterized in that: The mass fraction ω of the coating layer in the composite material C 1-8%.
6. The pre-lithiation silicon dioxide composite material with a core-shell structure according to claim 1, characterized in that: The gas generation amount L of the composite material is less than 0.2 mL / g.
7. The pre-lithiation silicon dioxide composite material with a core-shell structure according to claim 1, characterized in that: The coating layer is a carbon coating layer.
8. A method for evaluating the cycle performance of a pre-lithiation silicon dioxide composite material, characterized in that: The composite material comprises a core and a coating layer coated on the surface of the core, the core comprises pre-lithium silicon oxide, and the evaluation method comprises the following steps: The cycle performance index of the composite material is set to Y, Y = a(-D 50 2 +17D 50 -60)+b×d Si +c(-ω C 2 +7ω C )+dL, where a=0.2, b=-0.1, c=0.15, d=-0.5, D 50 is the particle size of the composite material, in μm, d Si is the particle size of silicon grains in the pre-lithiation silicon oxide, in nm, ω C is the mass fraction of the coating layer in the composite material, in %, and L is the gas production of the composite material, in mL / g; According to the particle size D of the composite material 50 , the particle size d of the silicon grains in the pre-lithiation silicon oxide Si , the mass fraction of the coating layer in the composite material ω C The gas production L of the composite material is used to calculate the cycle performance index Y of the composite material. The larger the Y is, the better the cycle performance of the composite material is.
9. The method for evaluating the cycle performance of the pre-lithiation silicon dioxide composite material according to claim 8, characterized in that: When Y is greater than or equal to 0.1, the number of cycles when the capacity of the composite material decays to 80% of the initial capacity is greater than or equal to 400 cycles; when Y is greater than or equal to 0.4, the number of cycles when the capacity of the composite material decays to 80% of the initial capacity is greater than or equal to 450 cycles; when Y is greater than or equal to 0.7, the number of cycles when the capacity of the composite material decays to 80% of the initial capacity is greater than or equal to 500 cycles.
10. The method for evaluating the cycle performance of the pre-lithiation silicon dioxide composite material according to claim 8, characterized in that: The method for determining the gas generation L of the composite material is as follows: the composite material with a mass of m is mixed with a binder and deionized water to obtain a test slurry and sealed, and the weight of the water displaced is tested by the drainage method to obtain the weight M1, and then after being placed at room temperature, the weight of the water displaced is tested by the drainage method again to obtain the weight M2, L = (M1-M2) / (ρ 水· m).